Diagnosing autism: Contemporaneous surveys of parent needs and paediatric practice. (3rd May 2016) - Hennel, Sabine; Coates, Cathy; Symeonides, Christos; Gulenc, Alisha; Smith, Libby; Price, Anna MH; Hiscock, Harriet
Abstract : Aim: Concurrence between parents' information needs and clinicians' practice when diagnosing autism is unknown but may influence families' uptake of management and adjustment. We aimed to1 compare parents' experience and preferences with paediatrician report of (i) diagnosis delivery and (ii) information given at diagnosis and2 identify types and usefulness of resources accessed by families post‐diagnosis. Methods: The design used for the study are parent and paediatrician surveys. Participants are parents of children aged 1.5–18 years, diagnosed with autism between 01 January 2010 and 30 September 2012 and their paediatricians who are members of the Australian Paediatric Research Network. Study‐designed quantitative and qualitative questions about diagnosis delivery and information given at diagnosis (written and spoken vs. neither) and parent perceived importance and harms of information accessed post‐diagnosis. Results: Paediatricians (53/198 (27%)) identified 1127 eligible families, of whom 404 (36%) participated. Parents were more likely to report receiving adequate time to discuss diagnosis than paediatricians (71 vs. 51%). Parents (98%) rated information about accessing allied health professionals and the meaning of diagnosis as most important, yet paediatricians offered written or spoken information about each infrequently (allied health: 22%; diagnosis: 42%). Post‐diagnosis, allied health was the most important source of information (83%). Harmful resources conveyed helplessness or non‐evidenced‐based therapies, but few parents (14%) reported this. Conclusions: Parents want more information than can be conveyed in a single diagnostic consultation. Developing a tailored 'autism action plan' with written materials could improve parents' understanding of and satisfaction with children's autism diagnoses.